Ocorrências e usos do Tucumã (astrocaryum vulgare mart) em comunidades ribeirinhas, quilombolas e de agricultores tradicionais no município de Irituia, Pará - Lima, Lucas Peranovichi e [UNESP]; Guerra, Gutemberg Armando Diniz; Ming, Lin Chau [UNESP]; Macedo, Magno Roberto Alves [UNESP] (My University, 2013)
The aim of the study is to demonstrate the occurrence and usage of the Tucumã (Astrocaryum vulgare Mart.) in rural areas of the Municipality of Irituia, in the State of Pará (Brazil), since the use of the palm part of the traditional culture of communities of farmers, riparian and quilombola, used in curing diseases in human and domestic animals, building shelters, obtaining fibers, production of tools and crafts, hunting and fishing. In addition to the uses reported by the population, tucumã has potential for the production of oil and biodiesel. In this sense, the Federal University of Pará – UFPA, in a partnership with the Irituia’s Municipal Government, is studying the implementation of an oleaginous processing plant in the municipality, among them, and includes the Tucumã as a potential source. Such proposal stipulates the production in the agroforestry system, as an alternative to the slash and burn agriculture in the region, reconciling environmental conservation with territorial rural development. Considering the results obtained in the field, it has been found an average of 9.4 stumps per hectare, each stump having 7.7 stipes and 4.7 racemes with up to 146 fruits. If all the Tucumã’s stumps were kept until they reached their average productivity capacity, it is estimated that the fruit production in the rural area of the municipality would be around 132.060 tons, which could produce up to 12.665,4 tons/year of pulp oil and 4.768,4 tons/year of nut oil, confirming the supply of raw material to move this productive chain.

Le sujet de cet article est demontrer l’ocurrence et les usages du tucumã (Astrocaryum vulgare Mart) dans la zone rurale du municipe d’Irituia, dans l’État du Pará, une fois que le profit de ce palmier fait partie de la culture traditionnelle des communautés des agriculteurs familiaux, des riverains et des descendents des esclaves. Ce palmier est aussi utilisé comme medicine pour maladies, dans l’alimentation humaine, comme nourriture pour des animaux doméstiqués, pour la construction des logements, pour l’obtention de fibres, pour la production d’outils et l’artisanat, pour la chasse et la pêche. Plus que des usages indiqué par la population locale, le tucumã a le potentiel pour la production d’huile de palme et le biodiesel. Dans ce sens, l’Université Fédérale du Pará – l’UFPA, en partenariat avec la Mairie d’Irituia, a promu des études pour l’implantation d’une usine pour la transformation des oleagineuses existentes dans le territoire de la municipalité, entre lesquelles s’est inclu le tucumã comme potentielle matière première. Cette proposition incite la production des sistèmes agroforestières comme une alternative au sistème d’abbatis-brûlis, en conciliant la conservation environementale avec le Développement Rural Territorial. Aprés les mensurations sur le terrain, on peut estimer une moyenne de 9,4 souches de tucumã par hectare, chaque souche avec 7,7 estipes et 4,7 regimes avec jusqu’à 147 fruits dans chaque regime. Si toutes les souches de tucumã restent maintenus jusqu’à atteindre cette moyenne de production, on estime que la production totale d’Irituia serait au tour de 132 060 tones, qui pourraient être transformé en 12 665,4 tones/année de huile de la pulpe et 4 768,4 tones/année de huile des amandes, ce qui confirmerait la matière première pour mouvementer toute cette chaine de production.

O objetivo deste trabalho é demonstrar as ocorrências e usos do tucumã (Astrocaryum vulgare Mart.) na zona rural do município de Irituia, no Estado do Pará, uma vez que o aproveitamento da palmeira faz parte da cultura tradicional de comunidades de agricultores familiares, ribeirinhas e quilombolas, utilizada na cura de doenças, na alimentação humana e de animais domésticos, construção de abrigos, obtenção de fibras, produção de utensílios e artesanatos, caça e pesca. Além dos usos relatados pela população, o tucumã possui potencial para a produção de óleo e biodiesel. Nesse sentido, a Universidade Federal do Pará – UFPA, em parceria com a Prefeitura Municipal de Irituia, estuda a implantação de uma usina para processamento de oleaginosas no município, entre as quais se inclui o tucumã como potencial matéria prima. Esta proposta estimula a produção em sistemas agroflorestais, alternativa ao sistema de agricultura de derruba e queima, conciliando a conservação ambiental com o Desenvolvimento Rural Territorial. Considerando os resultados obtidos em trabalho de campo, podem ser estimadas em média 9,4 touceiras de tucumã por ha, cada touceira possuindo 7,7 estipes e 4,7 cachos com até 146 frutos. Se todas as touceiras de tucumã forem mantidas até que atinjam esta capacidade de produção média, estima-se que a produção de frutos na área rural do município será em torno de 132.060 toneladas, que poderão produzir até 12.665,4 toneladas/ano de óleo da polpa e 4.768,4 toneladas/ano de óleo das amêndoas, confirmando a oferta de matéria prima para movimentar essa cadeia produtiva.
Occurrence and uses of tucumã (astrocaryum vulgare mart.) in riverine, quilombola and traditional farmers in the municipality of irituia– state of Pará, Brazil
Occurrence et usages du tucumã (astrocaryum vulgare mart.) en communautes riveraines, quilombolas et des agriculteurs traditionnels dans la municipalite d’irituia, Para
Keywords: Agro-exploration; Oleaginous; Traditional agriculture; Local knowledge; Sustainable developmen; Agroextraction; Oleagineuses; Agriculture traditionelle; Savoirs locaux; Développement durable; Agroextrativismo; Oleaginosas; Agricultura tradicional; Saberes locais; Denvolvimento sustentável